2017
DOI: 10.1097/md.0000000000009119
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis to compare success rates of retrograde intrarenal surgery versus percutaneous nephrolithotomy for renal stones >2 cm

Abstract: Background:We performed a systematic review and meta-analysis comparing stone-free rates between retrograde intrarenal surgery (RIRS) and percutaneous nephrolithotomy (PCNL), using updated, more reliable evidence.Materials and methods:Randomized controlled trials comparing RIRS and PCNL for >2 cm stones were identified from electronic databases. Stone-free rates for the procedures were compared by qualitative and quantitative syntheses (meta-analyses). Outcome variables are shown as risk ratios (RRs) with 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 29 publications
0
40
1
Order By: Relevance
“…Therefore, RIRS has been adopted as the preferred choice of management of kidney stones because of its low complication rate, especially for solitary kidney patients. Moreover, multiple studies demonstrated RIRS as an efficient and safe procedure which could be utilized to manage kidney stones in with solitary kidney patients [3,8,9,11]. From the study of 29 RIRS patients who were treated with renal stones by Giusti G et al…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, RIRS has been adopted as the preferred choice of management of kidney stones because of its low complication rate, especially for solitary kidney patients. Moreover, multiple studies demonstrated RIRS as an efficient and safe procedure which could be utilized to manage kidney stones in with solitary kidney patients [3,8,9,11]. From the study of 29 RIRS patients who were treated with renal stones by Giusti G et al…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…However, with advancing minimally invasive technology, RIRS is progressively being utilized as the best alternative therapy to PCNL for managing kidney stones owing to negligible complications. For solitary kidney patients, RIRS plays an essential role in preserving renal parenchyma [3,8,9]; nevertheless, lower SFR has been reported for large kidney stones [3,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Kang et al reported a systematic review and meta-analysis, in which updated evidence of stone-free rates of RIRS and PCNL in > 2-cm renal stones were compared with a previous report [54]. In their meta-analysis comparing the success (stone-free) rates between PCNL and RIRS, the forest plot using the random-effects model showed a risk ratio of 1.11 (95% CI: 1.02-1.21; p = .01) favoring PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Zheng et al reported no difference between RIRS and PCNL in > 2-cm renal stones using meta-analysis [55]. Kang et al concluded that their meta-analysis was performed using three additional articles compared with Zheng et al, and all three additional studies reported stone-free rates with RIRS that were relatively lower than those seen with PCNL [54]. Zhang et al…”
Section: Discussionmentioning
confidence: 99%
“…Among these three interventional treatments, PCNL is currently the most effective treatment option for renal stone >2 cm [2]. In the European Association of Urology Urolithiasis Guidelines, ESWL and RIRS are recommended as first-line treatment for renal stone <2 cm in length, and PCNL is recommended as a first-line treatment for renal stone ≥2 cm [3].…”
Section: Introductionmentioning
confidence: 99%